Towards an Empirical Understanding of membawa ‘bring’: Corpus Insights into Indonesian Light Verb Constructions - Nugraha, Danang Satria; Vincze, Veronika (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
This study analyzes the usage of the verb membawa (lit. bring) in Indonesian light verb constructions (LVCs). LVCs are ubiquitous in many agglutinative languages, including Indonesian. These constructions offer a unique way of combining a semantically light verb, which lacks inherent meaning, with another element to convey a specific concept. For instance, membawa pesan (lit. bring a message), membawa kemenangan (lit. bring a victory), membawa perasaan (lit. bring the feeling), membawa perubahan (lit. bring the change), amongst others. This study utilized corpus-based techniques to conduct a quantitative and qualitative analysis of 150 LVCs from the Indonesian-Leipzig Corpora Collection (ILCC) corpus. The findings of the study revealed three key points. Firstly, LVCs demonstrated a wide range of morphological and semantic usage, including primary and advanced areas, synonymic pair, and noun core proposition areas. Secondly, the morphosemantic relationships between core nouns in LVCs could be identified in the relations between base-abstract (0.15), base-concrete (0.37), affixed-abstract (0.36), and affixed-concrete (0.13). Thirdly, constructions with synonymic pairs dominated the total LVCs (0.75). However, all LVCs demonstrated the core proposition of the noun, which varied between ‘peoples’ (0.23), ‘materials’ (0.19), ‘objects’ (0.13), ‘qualities’ (0.17), ‘actions’ (0.11), and ‘processes’ (0.17). The findings suggest that LVCs in Indonesian are not merely syntactic constructions but rather reflect the intricate relationships between the verb and the noun, which can be analyzed in terms of their semantic and morphological properties. These findings can be applied to areas such as machine translation and computational linguistics, where a comprehensive understanding of LVCs is essential for accurate and effective language processing. Further corpus-based study could focus on analyzing the syntax and discourse functions of LVCs membawa.